PENGARUH KEPUTUSAN UTAMA TERHADAP NILAI PERUSAHAAN SEKTOR MANUFAKTUR YANG TERDAFTAR DI BEI TAHUN 2012-2016 - Tannia Tannia; Claryn Tanado; Elisa Putri (Journal of Business & Applied Management, 2018)
The purpose of this research is to determine effect of the main decisions on firm value ofmanufacturing companies listed in Indonesia Stock Exchange period, of 2012-2016. The main decisionsare three main functions of a financial manager in every firm. This research is a quantitative researchthat uses panel data and processing the panel data with E-Views. Sample of this research are 120manufacturing companies listed in Indonesia Stock Exchange.The results that there are a significanteffect of Dividend Decision on firm value and there is an insignificant effect of investment and fundingdecision of manufacturing companies listed in Indonesia Stock Exchange, period of 2012-2016.Key words: Investment, Funding, Dividend, Value of Firm